Drosophila adult and larval pheromones modulate larval food choice - Farine, Jean-Pierre (The Royal Society, 2014)
Insects use chemosensory cues to feed and mate. In Drosophila, the effect of pheromones has been extensively investigated in adults, but rarely in larvae. The colonization of natural food sources by Drosophila buzzatii and Drosophila simulans species may depend on species-specific chemical cues left in the food by larvae and adults. We identified such chemicals in both species and measured their influence on larval food preference and puparation behaviour. We also tested compounds that varied between these species: (i) two larval volatile compounds: hydroxy-3-butanone-2 and phenol (predominant in D. simulans and D. buzzatii, respectively), and (ii) adult cuticular hydrocarbons (CHs). Drosophila buzzatii larvae were rapidly attracted to non-CH adult conspecific cues, whereas D. simulans larvae were strongly repulsed by CHs of the two species and also by phenol. Larval cues from both species generally reduced larval attraction and pupariation on food, which was generally—but not always—low, and rarely reflected larval response. As these larval and adult pheromones specifically influence larval food search and the choice of a pupariation site, they may greatly affect the dispersion and survival of Drosophila species in nature.